2003
DOI: 10.1086/380418
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Claudin 16 Mutation Associated with Childhood Hypercalciuria Abolishes Binding to ZO-1 and Results in Lysosomal Mistargeting

Abstract: Mutations in the gene coding for the renal tight junction protein claudin 16 cause familial hypomagnesemia with hypercalciuria and nephrocalcinosis, an autosomal recessive disorder of renal Ca(2+) and Mg(2+) handling that progressively leads to chronic renal failure, with nephrolithiasis having been reported in heterozygous carriers. Screening a cohort of 11 families with idiopathic hypercalciuria identified a novel homozygous mutation in the claudin 16 gene in two families. In contrast to classical symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 28 publications
4
116
1
1
Order By: Relevance
“…Various mutations of PCLN-1 within the extracellular loops or the transmembrane domains have been identified in patients with FHHNC (4,19,20). Recently, Muller et al (21) reported a novel mutation at the C-terminal Thr residue of the PDZ-binding motif that inhibits the association of PCLN-1 with ZO-1 in patients with idiopathic hypercalciuria. So far, biochemical and cell biological characterizations of the PDZ-binding motif of PCLN-1 have not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mutations of PCLN-1 within the extracellular loops or the transmembrane domains have been identified in patients with FHHNC (4,19,20). Recently, Muller et al (21) reported a novel mutation at the C-terminal Thr residue of the PDZ-binding motif that inhibits the association of PCLN-1 with ZO-1 in patients with idiopathic hypercalciuria. So far, biochemical and cell biological characterizations of the PDZ-binding motif of PCLN-1 have not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of the PDZ-binding motif (YV) at the C terminus of claudin-1-8 was enough to inhibit the association of claudins with ZO-1, but the mutants could be still distributed at the TJ (9). On the contrary, PCLN-1 mutants with the substitution of Thr for Arg at the C terminus led to lysosomal mistargeting (21). We found that PCLN-1 mutants can be incorporated in TJ to some extent without binding to ZO-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It contains a PDZ-binding motif that enables claudins to directly interact with the tight junction-associated MAGUKs, ZO-1, ZO-2, and ZO-3 (53), with MUPP1 (40) and with PATJ (85). The interaction with cytoplasmic scaffolding proteins like ZO-1 indirectly links claudins to the actin cytoskeleton and most likely stabilizes them at the tight junction (77). The cytoplasmic tail upstream of the PDZ is required for targeting of claudins to the tight junctional complex (86) and a determinant of protein stability (105).…”
Section: Structure Of Claudinsmentioning
confidence: 99%
“…Although renal features like nephrocalcinosis were reported in heterozygous carriers of a CLDN19 gene mutation, 11 we were unable to find reported families in which a heterozygous carrier showed to have an evident hypercalciuria and low normal magnesemia but no other disease symptoms. This findings alert on the need to carefully explore the FHHNC clinical, laboratory, kidney ultrasonography, and mutation status in first degree relatives of patients with CLDN19 gene mutations to avoid unsuitable kidney donors.…”
Section: Discussionmentioning
confidence: 76%
“…9 Mutations in CLDN16 and CLDN19 occur throughout the coding region and can affect proper folding, intracellular trafficking of the protein, or its paracellular pore forming function. [11][12][13] Herein, we present the first case report of a Mexican family with three affected sisters carrying a p.Gly20Asp mutation in CLDN19.…”
Section: +mentioning
confidence: 99%